2002
DOI: 10.1111/j.2042-3306.2002.tb05430.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced tendon hypertrophy: cross‐sectional area changes during growth are influenced by exercise

Abstract: SummaryMost skeletal tissues are thought to adapt to the mechanical environment they experience. While this has been demonstrated for muscle and bone, previous studies in the mature horse have failed to demonstrate adaptation in the superficial digital flexor tendon (SDFT), which suffers a high frequency of injury. This study tested the hypothesis that imposed exercise during growth would result in an increase in SDFT cross-sectional area (CSA). Fourteen Thoroughbred foals were divided into 2 sex-matched group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
4
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 11 publications
(10 reference statements)
7
51
4
4
Order By: Relevance
“…Such thickening may be the result of a process of ligament degeneration caused by metaplasia of collagen fibers giving rise to infiltrators of chondrocytes, proliferation of fusiform cells similar to fibroblasts, infiltration of vessels and small ossifications 23 . In the research by Kasashima et al 15 , the results support the hypothesis that the imposition of additional physical activity, even after a long period of rest with little activity, did not result in compensatory activity of tendon tissue of ponies, but cumulative instead. This allows the reasoning of the stay of individuals, with little musculoskeletal capacity, before loads and in long periods, also considering suit therapy in home environment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Such thickening may be the result of a process of ligament degeneration caused by metaplasia of collagen fibers giving rise to infiltrators of chondrocytes, proliferation of fusiform cells similar to fibroblasts, infiltration of vessels and small ossifications 23 . In the research by Kasashima et al 15 , the results support the hypothesis that the imposition of additional physical activity, even after a long period of rest with little activity, did not result in compensatory activity of tendon tissue of ponies, but cumulative instead. This allows the reasoning of the stay of individuals, with little musculoskeletal capacity, before loads and in long periods, also considering suit therapy in home environment.…”
Section: Discussionsupporting
confidence: 77%
“…A study by Kasashima et al 15 with ponies demonstrated that there was an increase in the thickness of the superficial digital flexor tendon in groups that exercised daily with load for short periods, however long lasting. Previously, Fujie et al 16 had already observed in rabbits aging one to three months that the changes in mechanical dimensions and properties of patellar tendons, induced by mechanical stress, were higher in younger animals.…”
Section: Discussionmentioning
confidence: 99%
“…The training programme for each horse was another variable that could lead to anatomical structure modification for adaptive hypertrophic changes in the matrix composition, resulting in an increase of ligament CSA, which was assumed to be consistent throughout the life of the horse (Cherdchutham et al 2001;Kasashima et al 2002;Moffat et al 2008;Dyson et al 2017). For this reason, horses that follow or had followed the same training were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Overuse type of tendon injuries are among the most common musculoskeletal pathologies in recreational and competitive athletes; and the structural changes have been widely reported (1). Load-induced structural changes, especially hypertrophy, have been also studied in tendons of animals and healthy subjects (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). On the other hand, relevant data regarding asymptomatic athletes are scarce (6,10,12).…”
Section: öZetmentioning
confidence: 99%